Challenges to Demonstrating Efficacy When Translating Microwave Diagnostic Devices - O'Loughlin, Declan (My University, 2023)
Microwave interactions with biological tissues have been proposed and examined for medical diagnostics for over forty years, yet despite substantial academic and industrial interest, very few diagnostic devices are in clinical use. Drawing on evidence from the literature, several common challenges to clinical translation of microwave diagnostic devices are identified with a particular emphasis on clinical efficacy. This work highlights potential solutions and practical approaches from related fields to help bridge the translational gap.
2023 IEEE Conference on Antenna Measurements and Applications (CAMA)
PUBLISHED
Genoa, Italy
Keywords: medical devices; biomedical microwaves; performance evaluation; Next Generation Medical Devices; Medical Devices